Total Occlusion of the Internal Carotid Artery by Subacute In-Stent Thrombosis and Subsequent Spontaneous Recanalization After Stent-Assisted Coil Embolization - Cheol Young Lee (Neurointervention, 2011)
We present a 61-year-old female with an unruptured intracranial aneurysm on the left superior hypophyseal artery. The patient was treated with endovascular management, stent-assisted coil embolization. Multiple embolic infarction and total occlusion of the left internal carotid artery (ICA) was occurred one day later. At 14 days of heparinization, complete recanalization of the ICA and full recovery of neurologic symptoms were achieved. Stent-assisted coil embolization is not without risk of instent thrombosis and the subsequent embolism. The cause of subacute in-stent thrombosis and natural course were uncertain; however, the clinical course may potentially be fatal. Therefore, rapid diagnosis and proper treatment are recommended.